Contemporary Developments and Perspectives in International Health Security - Volume 1 2021
DOI: 10.5772/intechopen.93520
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Adulthood Chronic Disease and Adverse Childhood Experiences (ACEs): Implications Regarding Prevention and Promotion in International Health

Abstract: Several studies, including the innovative 1998 ACE Study by CDC-Kaiser Permanente, have assessed the association among adulthood chronic disease and the prevalence of maladaptive, health-harming behaviors including: excessive alcohol use, tobacco use, physical inactivity, psychiatric illness including suicidal ideation or attempts, promiscuous sexual behavior (>50 sex partners), history of STI/STD and severe obesity (obesity (BMI > 35 kg/m 2)), subsequent to an individual's exposure to adverse childhood experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Toxic stress was found to be associated with dysfunction of the allostatic systems, which include the nervous, endocrine, and immune systems (Boullier & Blair, 2018 ; Oral et al., 2016 ). ACEs have been found to increase the risk of chronic diseases (Anda et al., 2010 , 2008 ), mental illnesses (Anda et al., 2002 ; Bebbington et al., 2011 ), and premature death (Anda et al., 2009 ; Felitti et al., 1998 ; Holter et al., 2020 ; Merrick et al., 2017 ). Moreover, violence and substance abuse are strongly related to ACEs (Alhowaymel et al., 2021 ; Anda et al., 1999 ; Mersky et al., 2013 ; Nurius et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Toxic stress was found to be associated with dysfunction of the allostatic systems, which include the nervous, endocrine, and immune systems (Boullier & Blair, 2018 ; Oral et al., 2016 ). ACEs have been found to increase the risk of chronic diseases (Anda et al., 2010 , 2008 ), mental illnesses (Anda et al., 2002 ; Bebbington et al., 2011 ), and premature death (Anda et al., 2009 ; Felitti et al., 1998 ; Holter et al., 2020 ; Merrick et al., 2017 ). Moreover, violence and substance abuse are strongly related to ACEs (Alhowaymel et al., 2021 ; Anda et al., 1999 ; Mersky et al., 2013 ; Nurius et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…MTPC is an 8-week intervention that incorporates evidence-based elements from other MBIs with behavior change components (Gawande, To, et al, 2019) and explicitly cultivates inner compassion (Neff & Germer, 2013). Given the widespread prevalence of trauma in community health primary care centers and how multiple past traumas (e.g., adverse childhood experiences) can increase the prevalence of chronic illness and mental health disorders (Holter et al, 2020; Sanderson et al, 2021), MTPC was designed to be implemented in a trauma-informed way. A key assumption of a trauma-informed approach is that any participant could have experienced trauma, even those who have not previously disclosed PTSD.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, intrusive trauma-related memories may repeat compulsively or be experienced as if the event is currently in process (Radulovic, 2017). Research shows early exposure to ACEs, and related childhood toxic stress harms the developing brain and impacts brain chemistry, affecting control of aggressive or erratic impulses, and reducing access to coping skills in the face of obstacles or difficulties (Garner et al, 2012;Holter et al, 2020;Schore, 2003). Furthermore, multiple studies have documented that cumulative stress across one's lifespan for persons of color makes them more likely to develop complex-PTSD and other mental disorders.…”
Section: Biological Perspectivesmentioning
confidence: 99%
“…In a similar study that focused on the risk of premature mortality related to ACEs, researchers found a 20-year difference in life expectancy for children who did not receive treatment for their ACEs compared with those who did (Brown et al, 2009). Poor health outcomes, including premature mortality, were dosedependent and cumulative, with outcome severity related to higher ACE exposure (Holter et al, 2020;Hughes et al, 2017).…”
Section: Prior History Of Traumatic Eventsmentioning
confidence: 99%